The Influence of Macroeconomic Indicators on Non-Performing Financing in Islamic Banking Using Mudharabah, Musharakah, and Murabahah Contracts - Syarif, Fandi Achmad; Ismail, Rifki; Ali, Zulkarnain Muhammad (Jurnal Indonesia Sosial Sains, 2025)
This research aims to analyze the influence of macroeconomic indicators on non-performing financing in Islamic banking with Mudharabah, Musyarakah, and Murabahah contracts. This research uses a quantitative approach with the VAR/VECM method. The research data covers the years 2015 - 2018 and includes all Islamic banks in Indonesia. The research results indicate that the macroeconomic indicators that influence and determine non-performing financing, based on Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) tests, are as follows: for Mudharabah financing, Inflation, Industrial Production Index, and Exchange Rate according to IRF, and Inflation and Exchange Rate according to FEVD; for Musyarakah financing, Money Supply according to IRF, and Inflation according to FEVD; and for Murabahah financing, Inflation and Money Supply according to IRF, and Industrial Production Index, Exchange Rate, and Money Supply according to FEVD.